2019
DOI: 10.1039/c8nj03383h
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne reduced graphene oxide dispersed bio-polyesteramide nanocomposites: an approach towards eco-friendly anticorrosive coatings

Abstract: RGO dispersed waterborne soy polyester amide nanocomposites were formulated utilizing a solventless VOC free green approach for use as low cost anticorrosive coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Spectral Analysis. FTIR, 1 H NMR, and 13 C NMR spectra of HELuA and LMPEA confirmed the formation of PEA resin. The important absorption bands and peak values have been mentioned below.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Spectral Analysis. FTIR, 1 H NMR, and 13 C NMR spectra of HELuA and LMPEA confirmed the formation of PEA resin. The important absorption bands and peak values have been mentioned below.…”
Section: Resultsmentioning
confidence: 66%
“…The bare MS panel is very prone toward corrosion, and the rate of corrosion increases in the presence of chloride ions. The application of LMPEA and LMPEA/Ag nanocomposite coatings offers effective corrosion protection to the MS substrate by forming a good protective layer that separates metal surface from corrosive environments and also due to a tortuous pathway provided to water molecules by the presence of a nanofiller . A higher water contact angle value for nanocomposite coating suggests that the coating has good hydrophobicity rendered by the inclusion of nanofiller, which renders efficient barrier property to the coating surface to hinder the diffusion of corrosive electrolytes, thus conferring superior corrosion resistance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterborne graphene dispersions with lignin–OH is reported that this lignin–OH on graphene surface enhances the anticorrosive properties [ 199 ]. rGO has been dispersed in waterborne polyesteramide and used as an anti-corrosive coating material for carbon steel strips [ 200 ]. Graphene modified with 1,10-phenanthroline-5-amine helps to detect the corrosion of the steel at an early stage by forming a red complex with Fe 2+ [ 201 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Nevertheless, barrier properties provided by a binder are not able to provide full corrosion protection to a coating, and hence the anticorrosion performance is markedly improved when anticorrosion pigments, inhibitors or additives are included in the paint formulation or in the binder itself. In this sense, recently, waterborne polymer dispersions (acrylic, epoxy, polyurethanes, and hybrids systems) have been modified by including in the dispersions boron nitride nanoparticles/nanosheets [18][19][20][21], graphene oxide [22][23][24], polyaniline nanoparticles [25][26][27], nanoferrite [28], and carbon nanotubes [29] among others. In addition to that, for a long lasting and efficient corrosion protection of the coated material, the metal substrate is usually chemically pretreated to provide enhanced corrosion protection as well as to increase its adhesion to the organic coating.…”
Section: Introductionmentioning
confidence: 99%